Shuffling type of biological evolution based on horizontal gene transfer and the biosphere gene pool hypothesis. (June 2020) - Mikhailovsky, George; Gordon, Richard
Abstract: Widespread horizontal gene transfer (HGT) may appear a significant factor that accelerates biological evolution. Here we look at HGT primarily from the point of view of prokaryote clones, which we take as the descendants of a single cell, all of whom have exactly the same nucleotide sequence. Any novelty that emerges as a random mutation, creating a new clone, could either disappear before its first HGT, or survive for a period and be transferred to another clone. Due to the chain character of HGT, each gene with an adaptive mutation is thus spread among numerous existing clones, creating further new clones in the process. This makes propagation far faster than elimination, and such genes become practically immortal and form a kind of "biosphere gene pool" (BGP). Not all of these genes exist in every clone, and moreover not all of them are expressed. A significant fraction of the BGP includes of genes repressed by regulatory genes. However, these genes express often enough to be subject to natural selection. In a changing environment, both repressed and expressed genes, after transferring to another clone, may prove useful in an alternative environment, and this will give rise to new clones. This mechanism for testing repressed genes for adaptability can be thought as a "shuffle of a deck of genes" by analogy with shuffling a deck of cards. In the Archean and Proterozoic eons, both BGP and the operational part of each genome were rather poor, and the probability of incorporation of randomly expressed genes into the operational part of each genome was very small. Accordingly, biological evolution during these eons was slow due to rare adaptive mutations. This explains why the realm of prokaryotes as the sole organisms on Earth lasted so long. However, over about 3.5 billion years before the Phanerozoic eon, the BGP gradually accumulated a huge number of genes. Each of them was useful in a certain environment of past eras. We suggest that multicellular eukaryotes that appeared at the end of the Proterozoic eon could shuffle these genes accumulated in BGP via HGT from prokaryotes that live in these multicellular organisms. Perhaps this was the cause of the "Cambrian explosion" and the high (and increasing) rate of evolution in the Phanerozoic eon compared with the Archean and Proterozoic.